Age of Information in SWIPT-Enabled Wireless Communication System for 5GB; IEEE Wireless Communications; Vol. 27, iss. 5 - Ponnimbaduge Perera T. D. Tarindu Dilshan; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Pitas I. Ioannis; Garg S. Sahil (2020, 2020)
Title screen